Contribution to lichen microbiota of the colombian tropical dry forest (montes de maría, sucre) (2020)
We present the first inventory of lichenized fungi found in tropical dry forest fragments in Montes de María, department of Sucre. Through linear transects (100 x 10 m), we surveyed six localities: Colosó, Chalán, Toluviejo, Morroa, Ovejas, and San Onofre. In order to identify whether species represented new chorological records, geographic distribution data were obtained from specialized literature. A total of 93 species distributed in 40 genera and 21 families were identified. All species are new records for the department of Sucre and 22 for Colombia. In this way, we made a contribution to the knowledge of the lichen biota of the Colombian tropical dry forest.